Penataan Ruang Terbuka Hijau Perkotaan Di Kawasan Mikro Surabaya - Eddy Imam Santoso; Mahrus Ali; Yeni Ika Pratiwi (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2020)
The aim of the service is to increase togetherness and concern between residents and RT Management in the area of public facilities, organize public facilities as well as to dispel the notion that residents do not need public facilities so that some public facilities are "abandoned" and improve the quality of green open space so that it can be more beneficial for residents the community around RTH. The results of this community service activity will be carried out pending the availability of a budget which is self-help for the community in the 3 RW 4 Rungkut Menanggal Harapan Surabaya area or the results of soft loans or donors from residents or groups of residents who care about the Public Facilities management program in the 3 RW 4 Rungkut Menanggal Surabaya area.